2002
DOI: 10.1183/09031936.02.00211202
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of alveolar surfactant aggregatesin vitroandin vivo

Abstract: In acute lung injury, a decrease in surface-active large aggregates and an increase in the less surface-active small surfactant aggregates are observed. The objective of the current study was to determine if the increase in small aggregates interfered with the function of large aggregates, thereby independently contributing to lung dysfunction.Isolated large aggregates, small aggregates, and large aggregatezsmall aggregate combinations were analysed for in vitro surface activity utilizing a pulsating bubble su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…It has been demonstrated that in a pure phospholipid vesicle system, PEG at certain molecular weights and concentrations can induce a depletion-attraction force that promotes the formation of large phospholipid aggregates (30). Large aggregates are known to be more surface active than their smaller counterpart both in vitro (31) and in vivo (32). Theoretical study has established that the depletion attraction force is proportional to the aggregate radius (28).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that in a pure phospholipid vesicle system, PEG at certain molecular weights and concentrations can induce a depletion-attraction force that promotes the formation of large phospholipid aggregates (30). Large aggregates are known to be more surface active than their smaller counterpart both in vitro (31) and in vivo (32). Theoretical study has established that the depletion attraction force is proportional to the aggregate radius (28).…”
Section: Discussionmentioning
confidence: 99%
“…The animal experiments were performed with the approval of the Los Angeles Biomedical Research Institute at Harbor-UCLA Medical Center Institutional Animal Care and Use Committee. Anesthesia, surgery, lavage, ventilation, and monitoring used in this study are the same as previously described (8,23). Briefly, adult male Sprague-Dawley rats weighing 200 -225 g were anesthetized with 35 mg/kg sodium pentobarbital and 80 mg/kg ketamine by intraperitoneal injection, intubated, and ventilated with a rodent ventilator (Harvard Apparatus, South Natick, MA) with 100% oxygen, a tidal volume of 7.5 ml/kg, a positive end-expiratory pressure (PEEP) of 3 cmH 2O, and a rate of 60/min.…”
Section: Methodsmentioning
confidence: 99%
“…The large aggregate subfraction contains dense structures and apoproteins that are responsible for the surfaceactivity of surfactant and hence maintain alveolar stability. Lighter, vesicular forms of surfactant that are undergoing recycling or clearance from the lung and are less surface-active, are present in the small aggregate fraction (8). The subfractions of dunnart surfactant were resuspended in 2 ml of deionized water for analysis of surfactant proteins.…”
Section: Animalsmentioning
confidence: 99%